Care of Older Persons Emerging International Perspectives. - Shankardass, Mala Kapur (Routledge, 2024)
This book explores the implications and significant ethical, social, economic and health challenges that an ageing world population presents. It provides valuable insights on concerns related to providing, organizing, planning and managing care for older persons in both formal and informal settings. As the number of older persons increases rapidly around the globe, caring for them is a very important aspect of all ageing and aged societies. While in most countries the care of older persons is provided informally by family members, the changing social scene, family structures and work and employment patterns are leading many nations to create provisions for formal care through institutions or paid services of caregivers. This book offers perspectives on formal and informal care from countries such as Japan, the Netherlands, the USA, India, South Africa and Poland, among others. The essays in this book underline a rights-based approach and focus on ethical, social, economic, health and legal aspects of care as they pertain to the universal phenomena of ageing as well as the specific demographic and epidemiological realities of the selected countries. They discuss concerns such as long-term care provisions, catering to the needs of people affected by dementia, providing residential care, taking the needs of family care providers into account, the growing requirement for paid care workers and channelizing training of both skilled and semi-skilled care providers to suit the needs of older people. This volume would be of interest to scholars and those working in the fields of sociology, health studies, age and ageing, psychology, social work, medical sciences, nursing and public policy. It will also be useful to NGO sector workers, administrators, as well as grassroots workers involved with the care of older persons.
Keywords: Older people -- Care.; elektronické knihy; electronic books